THU0331 Tramadol Effects on Exercise Capacity in Patients with Low Back Pain. (10th June 2014) - Ionescu, A.M.; Popa, R.; Manolescu, B.N.; Tache, S.; Berteanu, M.; Badea, R.; Dumitru, L.; Savulescu, S.; Dinu, H.
Abstract : Background: Pain is one of the most important factors limiting exercise capacity. Low back pain is a very common problem and a major cause of disability among adults worldwide. The lifetime prevalence of non-specific low back pain is estimated at 60%>70% amoung industrialized countries. Tramadol is a centrally acting analgesic used all over the world to alleviate acute or chronic pain of moderate to severe intensity. In a previous experimental study it has been shown that tramadol improves exercise capacity, neuro-psychological state and oxidants/antioxidants balance in exercise trained rats. Objectives: Our study goal was to assess Tramadol effects on exercise capacity in patients with low back pain. Methods: A number of 16 patients with middle intensity non-specific low back pain joined the study for a period of 7 days. These patients were divided in two groups: test group (8 patients received 50 mg of tramadol twice a day for 7 days) and control group (8 patients received placebo following the same procedure and equivalent quantity). All patients were tested using cycle ergometer with progressively increasing work-rate exercise test at baseline and after 7 days of treatment. We investigated exercise duration (time), the moment of lactate threshold (LT), peak oxygen uptake (VO2 max), aerobic contribution to exercise and ventilatory efficiency for each patient at baseline and after 7 days. Results: The groups were homogenous regarding age and all evaluated parameters at baseline. Exercise duration and lactate threshold moment significantly improved for patients having received tramadol (p=0, 0039). Peak oxygen uptake, VO2 max was greater for test group but in a non-significant manner. Aerobic contribution to exercise improved for patients in test group (p=0, 0195) and was significantly lower in control group (p=0, 0039). Ventilatory efficiency also improved for test group at the end of the study (p=0, 0078). Conclusions: Tramadol administration to patients with low back pain improved exercise capacity and effort tolerance. References: www.who.int Tache S, Staicu LM. The organism adaptation to physical exercise. Risoprint Ed. Cluj-Napoca; 2011. David CT, David I, Tache S, Moldovan R. Tramadol influence upon maximal aerobe exercise capacity and upon pain threshold on traine rats. IIIrd Millenium Palestrica. 2007; 28(2):108-112. Barrett KE, Barman SM, Boitano S, Brooks HL. Ganong's Review of Medical Physiology, ed. 23a. Ed. McGraw Hill, Singapore. 2010; 167-171. Ionescu AM, Tache S, Berteanu M. Biochemichal and physiological basis of muscle pain. IIIrd Millenium Palestrica. 2012; 13(1):48-51. Wassermann K et al. Principles of exercise testing and interpretation, 5th ed. Lippincott W&W, Philadelphia. 2012 Ionescu AM, Tache S. Effects of acute administration of Tramadol upon effort capacity in rats. IIIrd Millenium Pastrica. 2011; 12(1): 11-14. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1439